ENDORPHINE MASSAGE INTERVENTION ON MOTHERS POST-SECTION CAESAREAN PAIN LEVEL CHANGES - Amalia Shabrina; Joanggi Wiriatarina Harianto; Pipit Feriani; Tri Wahyuni (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Cesarean delivery is a surgical intervention frequently associated with postoperative discomfort stemming from abdominal and uterine incisions. Inadequately managed pain following this procedure may hinder early mobilization, interfere with lactation, delay overall recovery, and elevate the probability of adverse outcomes such as thromboembolism and compromised maternal-infant attachment. Endorphin massage serves as a viable therapeutic modality, utilizing gentle, rhythmic tactile stimulation designed to prompt the secretion of endogenous analgesic peptides known as endorphins. This technique functions by fostering relaxation, decreasing muscular rigidity, enhancing hemodynamics, and mitigating pain perception via specific neurophysiological pathways. Purpose: The objective of this investigation was to evaluate the efficacy of endorphin massage in diminishing pain severity among postpartum women who have undergone a Cesarean section. Methods: This inquiry utilized a case study framework grounded in the examination of clinical nursing practice. The intervention comprised a 15-minute endorphin massage session administered once daily over a consecutive three-day period. Data acquisition involved patient history taking, direct observation, and clinical documentation, with post-surgical pain assessments conducted utilizing the Numeric Rating Scale (NRS), the Visual Analogue Scale (VAS), and the Indonesian Nursing Outcome Standards (SLKI) criteria. Results: The findings demonstrated that the application of endorphin massage effectively lowered pain intensity in patients recovering from Cesarean deliveries. Consequently, this technique represents a practical, non-pharmacological nursing strategy for managing post-cesarean pain. Conclusion: Administering a 15-minute endorphin massage daily for three days successfully alleviated pain intensity in post-Cesarean section individuals. Pain metrics, as evaluated by the NRS and VAS, dropped from a baseline score of 5 on the initial day to a score of 1 following the final session on day three. Additionally, nonverbal pain indicators, including facial grimacing and guarding of the abdomen post-coughing, were notably diminished. Thus, endorphin massage is recommended as an adjunctive, non-pharmacological therapy for alleviating postoperative discomfort in post-Cesarean mothers.